2020
DOI: 10.1177/1937586720970198
|View full text |Cite
|
Sign up to set email alerts
|

From Fable to Reality at Parkland Hospital: The Impact of Evidence-Based Design Strategies on Patient Safety, Healing, and Satisfaction in an Adult Inpatient Environment

Abstract: Objective: This research aimed to evaluate the quantitative effects of new hospital design on adult inpatient outcomes. Background: Tenets of evidence-based healthcare design, notably single-patient acuity-adaptable and same-handed rooms, decentralized nursing stations, onstage offstage layout, and access to nature were expected to promote patient healing and increase patient satisfaction, while decreasing adverse events. Methods: Patient healing was operationalized through length of stay (LOS) and patient saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The new facility is nearly double the size of the old facility; for example, units in the old facility mainly consisted of shared patient rooms at 218 sqft per room separated by narrow hallways. In contrast, units the new facility have 36 single-patient rooms at 310 sqft organized in a racetrack configuration; further details of the floor plan can be found elsewhere (Brittin et al, 2019; Rich et al, 2021). Parkland Hospital serves more than 1 million outpatient visits and over 300,000 urgent and emergent care visits per year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The new facility is nearly double the size of the old facility; for example, units in the old facility mainly consisted of shared patient rooms at 218 sqft per room separated by narrow hallways. In contrast, units the new facility have 36 single-patient rooms at 310 sqft organized in a racetrack configuration; further details of the floor plan can be found elsewhere (Brittin et al, 2019; Rich et al, 2021). Parkland Hospital serves more than 1 million outpatient visits and over 300,000 urgent and emergent care visits per year.…”
Section: Methodsmentioning
confidence: 99%
“…In the early years of the project cycle, the study site was a Pebble Partner Hospital, participating in the EBD process promoted by the Center for Health Design (www.healthdesign.org). The facility is strategically oriented toward research and is affiliated with an academic institution; as such, the hospital advocates the setting as an opportunity for research to understand impacts of healthcare design, and how these design advancements lead to improved outcomes (Brittin et al, 2019; Rich et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…At the time of a recent systematic literature review focused on patient and staff outcomes related to the incorporation of decentralized nursing stations, no study had statistically measured an effect on any patient outcome (Jimenez et al, 2019), and updated searches revealed only Real et al (2018) and Rich et al (2020) have done so since. Rich et al (2020) measured changes in patient outcomes of healing, safety, and satisfaction following the implementation of evidence-based design strategies, including a shift to decentralized nursing stations, and found a positive impact on satisfaction but no direct effect on quality outcomes. An earlier study by Hua and colleagues (2012) also aimed to connect decentralized inpatient unit design to similar patient outcomes using hospital records data and scores from standardized patient satisfaction surveys.…”
mentioning
confidence: 99%